Exploring the infrared gluon and ghost propagators using large asymmetric lattices - Oliveira, O. (2007)
We report on the infrared limit of the quenched lattice Landau gauge gluon propagator computed from large asymmetric lattices. In particular, the compatibility of the pure power law infrared solution (q2)2k of the Dyson- Schwinger equations is investigated and the exponent k is measured. The lattice data favours k » 0:52, which would imply a vanishing zero momentum gluon propagator as predicted by the Kugo-Ojima confinement mechanism and the Zwanziger horizon condition. Results for the ghost propagator and for the running coupling constant are shown.